THE IMPORTANCE OF REPETITION IN CONTEMPORARY EDUCATIONAL TECHNOLOGIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article presents the conditions, forms, methods, means and ways of using new pedagogical technologies in teaching physics in secondary specialized educational institutions.